Przygotowanie dziecka w wieku przedszkolnym do kształcenia muzycznego = Preparing a preschool child for music education - Kumik, Ewa (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The family is important in early childhood musical development. The values and atitudes conveyed in it should be continued in the educational institutions. The author draws attention to the various aspects of preparing a young child to learn in a music school by discussing the family environment and early childhood education. Skills acquired at preschool level are more rewarding in school and better in professional and social life in adult life.
Keywords: rozwój muzyczny dziecka; formy aktywności muzycznej; musical development of a child; the form of musical activity